Investigating the lap shear adhesion of coir and glass-fibre reinforced epoxy bonding to mild steel with varying volume fractions - Alajmi, Ayedh Eid; Alsaeed, Talal; Alotaibi, Jasem Ghanem; Srelam, Jayanth Kumar; Yousif, Belal F. (Frontiers in Mechanical Engineering, 2023)
Bonding synthetic fibres to metals to improve strength, durability, and corrosion resistance is a prevalent practise in the automotive, marine, and aerospace industries.Lap shear adhesion, a measurement of the bonding strength between composites and metallic substrates, is essential for structural integrity. The emergence of natural fibre composites as sustainable alternatives to synthetic composites makes it essential to investigate their lap shear behaviour and the effect of fibre volume fraction on composite properties. This research investigates the adhesion behaviour of coir and glass fibre epoxy composites to mild steel. Coir fibres, which are known for their resilience and tenacity, were treated with an alkaline solution to improve their adhesion to the resin.Samples of lap shear adhesion were prepared in accordance with ASTM specifications, and tests were conducted using a tensile machine. Increasing the volume fraction of coir or glass fibres decreased the bond strength, as demonstrated by the results. Due to the fibres' greater tensile strength and rigidity, glass fibre composites exhibited superior strength. However, under tensile loading conditions, coir fibres exhibited superior adhesion to mild steel surfaces. SEM micrographs confirmed that coir composites exhibit shear failure while glass composites exhibit fibre pull-out behaviour. This study concludes by highlighting the engineering potential of coir fibres, considering their natural properties and cost-effectiveness. It is necessary to further optimise the fibermatrix interface and comprehend the mechanical behaviour of coir composites in order to maximise their effectiveness. To assure the long-term durability of composite-metal joints, surface preparation, adhesive type, application procedure, and environmental conditions must also be considered. At a content percentage of 10%, glass fibres exhibited 100% higher shear strength compared to coir fibres in epoxy composites.Conversely, coir fibres at 10% content demonstrated approximately 75% greater shear strength than the values obtained with 40% glass fibres. The failure mechanisms observed are delamination or fibre fracture in the bonding area under tensile and shear loading. Increasing the fibre volume fraction reduces bond strength. Factors such as limited space for the matrix, tension concentrations, and the mechanical properties of the fibres contribute to weakened bonds.